Dasar Program Perencanaan Dan Perancangan Arsitektur (Dp3a)Pengembangan Jalan Raya Sukowati Sebagai Kawasan City Walk Sragen - FEBRIANTO, ANANG; , Dr. Ir. Qomarun, MM (2016)
Jalan Raya Sragen is the road protocol along Sragen, which is one potential area because there are many shops, markets, schools and town square that is located in the center of Sragen and a strategic road which is the main street of Solo-Sragen and also is the main road to Ngawi directly bordering Central Java and East Java. Methods through observation or survey to the field, literature, data processing, data analysis in order to obtain the result of design development Highway Sragen is more comfortable for the pedestrians, disabled people and for the user. The purpose of the Design Development Highway Sragen as City Walk Sragen district is developing a pedestrian path or area City Walk are already on the road Sragen, in order to create the comfort and safety of motor vehicles for pedestrians and disabled people and the surrounding communities. With the arrangement of street furniture with an ancient concept because Sragen famous museum also famous for its ancient and batik Sragen so that the paving-shaped arrangement of the motif.